A novel hybrid supervised artificial neural network (ANN) for data visualization and classification to the application of mental disorder diagnosis - Md. Sarwar, Zahan Tapan (2008)
The objective of this research was set to propose a supervised ANN method able to perform data classification and data structure, inter-neuron distances and data topology preserved visualization simultaneously. A real world application of mental disorder diagnosis in counseling domain was then investigated and LVQ with AC was employed to facilitate classification and visualization in designing and development of an intelligent decision support system to assist counselors in diagnosis of mental disorders.